Women in the Reformation Era - Pangestu, Ahmad Dimas Jihan; Mahfud (SINGOSARI: Jurnal Perkumpulan Prodi Pendidikan Sejarah Se-Indonesia (P3SI) Wilayah Jawa Timur, 2024)
This article discusses the role of women in the context of social, political, and economic changes during the reform era in Indonesia. The reform era, which began in 1998, marked a   significant   transition   in   the   political   and   social   life   of   Indonesia,   introducing democratization, decentralization, and  civil  freedoms.  In  this  framework,  Indonesian women  faced  new  challenges  and  opportunities  in  various  sectors,  including  politics, education, economy, and culture. Although gender gaps still exist, women have gained greater access to strategic positions and have played an active role in policymaking. This article analyzes the development of women's rights, the challenges they face, and their contributions to strengthening Indonesia's democratic system post-reform.